2021
DOI: 10.1007/s11845-021-02569-4
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of COVID-19 on ear, nose and throat (ENT) specialists

Abstract: Introduction Ear, nose and throat (ENT) specialists are a high-risk group for COVID-19. Although the implications of SARS-CoV-2 infection on physical health are well-documented, the psychological impact is frequently overlooked. Aims The aim of this study was to gauge the psychological impact of COVID-19 on ENT specialists in Ireland. Methods A national, cross-sectional, web-based survey was distributed to ENT specialists during the peak of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…An Irish survey of 38 ENT specialists found that 34% ( n = 13) screen positive for anxiety, and 84% ( n = 32) felt that they had increased exposure to the virus compared with other specialties, with 32% (=12) feeling unable to protect themselves from Covid‐19. 24 The rates of burnout and increased risk of poor outcomes for 684 orthopedic surgeons in a cross sectional survey across five countries was found to be high irrespective of healthcare system. 25 This has important repercussions for bariatric surgeons who may experience parallel issues in terms of the context specificity of their own work.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…An Irish survey of 38 ENT specialists found that 34% ( n = 13) screen positive for anxiety, and 84% ( n = 32) felt that they had increased exposure to the virus compared with other specialties, with 32% (=12) feeling unable to protect themselves from Covid‐19. 24 The rates of burnout and increased risk of poor outcomes for 684 orthopedic surgeons in a cross sectional survey across five countries was found to be high irrespective of healthcare system. 25 This has important repercussions for bariatric surgeons who may experience parallel issues in terms of the context specificity of their own work.…”
Section: Discussionmentioning
confidence: 95%
“…Ear, Nose and Throat (ENT) specialists are a high‐risk group for Covid‐19 and potentially increased psychological harm. An Irish survey of 38 ENT specialists found that 34% ( n = 13) screen positive for anxiety, and 84% ( n = 32) felt that they had increased exposure to the virus compared with other specialties, with 32% (=12) feeling unable to protect themselves from Covid‐19 24 . The rates of burnout and increased risk of poor outcomes for 684 orthopedic surgeons in a cross sectional survey across five countries was found to be high irrespective of healthcare system 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of anxiety in our study are in accordance with results from previous surveys which used self-report questionnaires validated in general population. The prevalence of anxiety in ENT-HCWs from previous studies are 38% by General Anxiety Disorder scale (GAD-7), 2 29.18% by Zung Self-rating Anxiety Scale, 3 and 7.8% measured by the Coronavirus Anxiety Scale (CAS). 7 To our knowledge, this is the first survey in ENT-HCWs using a newly developed screening tools for stress and anxiety among HCWs in response to viral epidemics, the SAVE-9.…”
Section: Discussionmentioning
confidence: 99%
“…Frontline healthcare workers (HCWs) in Otorhinolaryngology or Ear Nose Throat (ENT) had high prevalence of stress, anxiety and depression during COVID-19 pandemic. [1][2][3][4] As there are growing demand on clinical works of ENT-HCWs during and after the COVID-19 pandemic, it is important to understand their stress, anxiety, and associated factors so that further mental health promotion or intervention programs can be designed and implemented. This study aims to explore stress and anxiety among ENT-HCWs during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, waiting lists in ENT are long, and many patients wait months for appointments, with some unfortunately waiting several years. Over 50,000 patients are on an otolaryngology waiting list, with over 20,000 scheduled to wait more than 18 months for an appointment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%